Predictive Analytics for Hurricane Forecasting by Utilizing Machine Learning Techniques - Khan, Aranya (Digital Repository of Theses, 2026)
Hurricanes are mature tropical storm system that develops under specific conditions in the North Atlantic, Northeast Pacific, and South Pacific Ocean regions. It is meteorologically a warm-core tropical atmospheric system without fronts, consisting of organized thunderstorm activity together with wind patterns that are mostly circular around a powerful core. In the meteorological classification, to be a hurricane, winds must be blowing continuously at a minimum speed of 74 mph (64 knots or 119 km/h), which is equivalent to Category 1 in the Saffir-Simpson scale.(Sanabia and Jayne, 2020). Hurricanes represent one of nature's most destructive phenomena, capable of causing catastrophic loss of life, widespread infrastructure damage, and economic disruption measured in billions of dollars. These powerful tropical cyclones form over warm ocean waters and can generate sustained winds exceeding 74 mph, massive storm surges that inundate coastal regions, and torrential rainfall leading to devastating inland flooding. The increasing frequency and intensity of these storms, potentially linked to climate change, have made accurate hurricane forecasting not merely a scientific challenge but a critical imperative for public safety and disaster preparedness(Kim et al., 2016). Traditional hurricane forecasting methods have relied primarily on numerical weather prediction models, which simulate atmospheric physics through complex mathematical equations. While these conventional approaches have achieved notable improvements over the past decades, they still face significant limitations in accuracy, particularly regarding rapid intensification events, precise landfall predictions, and long-range forecasting(Lockwood et al., 2022). The inherent complexity of atmospheric dynamics, coupled with the chaotic nature of weather systems, creates substantial uncertainties that can leave communities inadequately prepared for incoming storms.